GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Toxicity of crude oil-derived polar unresolved complex mixtures to Pacific herring embryos: Insights beyond polycyclic aromatic hydrocarbons - Maxwell L. Harsha; Yanila Salas-Ortiz; Alysha D. Cypher; Ed Osborn; Eduardo Turcios Valle; Jacob L. Gregg; Paul K. Hershberger; Yuri Kurerov; Sarah King; Aleksandar I. Goranov; Patrick G. Hatcher; Anastasia Konefal; et al. (Science of The Total Environment, 2024)

Comparison of infrared thermography of the blowhole mucosa with rectal temperatures in killer whales (Orcinus orca) - Jennifer P. Russell; Micah St. Germain; Steve D. Osborn; Todd L. Schmitt; Kelsey E. S. Herrick; Todd Robeck (Frontiers in Marine Science, 2024)
Killer whales are an important sentinel species and developing non-invasive methods of health assessments might provide insight for understanding how wildlife health is influenced by ecosystem change. Rectal temperature (RT) is a proxy for core body temperature in managed-care cetaceans, however, this measurement is impractical for free-ranging cetaceans and infrared imaging has been suggested as an alternative. The aim of the current study was to prospectively compare infrared thermography of the blowhole to rectal temperatures in killer whales, as well as establish a healthy range for rectal temperature using retrospective data. Infrared video was recorded from the blowhole of thirteen healthy killer whales in managed care, immediately followed by rectal temperature measurement. Repeated measures Bland-Altman analysis revealed blowhole temperature (BHT) had a bias of -1.28°C from RT. Considerable proportional bias was observed with agreement between measurements improving as mean temperature increased. RT positively associated with air temperature, and inversely associated with body mass. BHT was not significantly affected by sex or body mass but was significantly affected by water temperature and air temperature. Retrospective analysis from eighteen killer whales (n = 3591 observations) was performed to generate expected RT ranges, partitioning out for sex and body mass. Given the proportional bias observed with Bland Altman analysis, BHT cannot currently be recommended as a measurement for absolute core body temperature, however infrared thermography of the blowhole remains a promising tool for health assessment of free-ranging killer whale populations, as it may serve as a non-contact screening tool to detect pyrexic animals within a group.

Quantifying exposure biases in early instrumental land surface air temperature observations - Emily J. Wallis; Timothy J. Osborn; Michael Taylor; Philip D. Jones; Manoj Joshi; Ed Hawkins (International Journal of Climatology, 2024)
Exposure biases are a pervasive non‐climatic change in land air temperature records which have been introduced as a result of changes in the way thermometers were sheltered from solar radiation and the elements over time. Exposure biases have not been widely accounted for in observational records, due to difficulties detecting/correcting the bias using traditional homogenisation techniques; therefore, exposure biases still contribute significant uncertainty to the early period in global temperature compilations. Here, an empirical approach to address the bias arising from the introduction of Stevenson‐type screens from the late‐19th century is presented. The approach consists of: (1) an empirical analysis of 54 parallel measurement series to identify the characteristics of the exposure bias in four exposure classes; (2) the development of bias‐estimation models based on an analysis of which variables influence the bias; and (3) the application of the models to an extended version of CRUTEM5 (CRUTEM5_ext), based on exposure metadata, to quantify and reduce the bias. Step one identified differences between the temperatures recorded in Stevenson screens and early exposures, which vary seasonally, diurnally, and with location and exposure class. The largest biases (in mean temperatures) were found in freestanding exposures (up to −0.78°C annually) and in summer, while the smallest biases were generally found in wall‐mounted exposures (near‐0°C annually) and in winter. Significant relationships between the bias and temperature, downward top of atmosphere and/or received shortwave downward solar radiation were found in each exposure class and led to the development of three regression‐based bias‐estimation models. Application of these models to 1,960 mid‐latitude stations in CRUTEM5_ext, resulted in small (≤0.016°C) positive adjustments to the Northern Hemisphere mid‐latitude mean before 1880, and larger (≤−0.1°C) negative adjustments to the Northern and Southern Hemisphere mid‐latitude means between 1882–1934 and 1856–1900, respectively. Larger adjustments were estimated regionally: up to −0.57°C annually and −0.79°C seasonally in individual grid cells.

Risks associated with global warming of 1.5 to 4 °C above pre-industrial levels in human and natural systems in six countries - R. Warren; J. Price; N. Forstenhäusler; O. Andrews; S. Brown; K. Ebi; D. Gernaat; P. Goodwin; D. Guan; Y. He; D. Manful; Z. Yin; et al. (Climatic Change, 2024)
The Topical Collection “Accrual of Climate Change Risk in Six Vulnerable Countries” provides a harmonised assessment of risks to human and natural systems due to global warming of 1.5–4 °C in six countries (China, Brazil, Egypt, Ethiopia, Ghana, and India) using a consistent set of climate change and socioeconomic scenarios. It compares risks in 2100 if warming has reached 3 °C, broadly corresponding to current global greenhouse gas emission reduction policies, including countries’ National Determined Contributions, rather than the Paris Agreement goal of limiting warming to ‘well below’ 2 °C and ‘pursuing efforts’ to limit to 1.5 °C. Global population is assumed either constant at year 2000 levels or to increase to 9.2 billion by 2100. In either case, greater warming is projected to lead, in all six countries, to greater exposure of land and people to drought and fluvial flood hazard, greater declines in biodiversity, and greater reductions in the yield of maize and wheat. Limiting global warming to 1.5 °C, compared with ~ 3 °C, is projected to deliver large benefits for all six countries, including reduced economic damages due to fluvial flooding. The greatest projected benefits are the avoidance of a large increase in exposure of agricultural land to severe drought, which is 61%, 43%, 18%, and 21% lower in Ethiopia, China, Ghana, and India at 1.5 °C than at 3 °C, whilst avoided increases in human exposure to severe drought are 20–80% lower at 1.5 °C than 3 °C across the six countries. Climate refugia for plants are largely preserved at 1.5 °C warming in Ghana, China, and Ethiopia, but refugia shrink in areal extent by a factor of 2, 3, 3, 4, and 10 in Ghana, China, India, Ethiopia, and Brazil, respectively, if warming reaches 3 °C. Economic damages associated with sea-level rise are projected to increase in coastal nations, but more slowly if warming were limited to 1.5 °C. Actual benefits on the ground will also depend on national and local contexts and the extent of future investment in adaptation.

Quantification of meteorological drought risks between 1.5 °C and 4 °C of global warming in six countries - Jeff Price; Rachel Warren; Nicole Forstenhäusler; Craig Wallace; Rhosanna Jenkins; Timothy J. Osborn; D. P. Van Vuuren (Climatic Change, 2022)
We quantify the projected impacts of alternative levels of global warming upon the probability and length of severe drought in six countries (China, Brazil, Egypt, Ethiopia, Ghana and India). This includes an examination of different land cover classes, and a calculation of the proportion of population in 2100 (SSP2) at exposed to severe drought lasting longer than one year. Current pledges for climate change mitigation, which are projected to still result in global warming levels of 3 °C or more, would impact all of the countries in this study. For example, with 3 °C warming, more than 50% of the agricultural area in each country is projected to be exposed to severe droughts of longer than one year in a 30-year period. Using standard population projections, it is estimated that 80%-100% of the population in Brazil, China, Egypt, Ethiopia and Ghana (and nearly 50% of the population of India) are projected to be exposed to a severe drought lasting one year or longer in a 30-year period. In contrast, we find that meeting the long-term temperature goal of the Paris Agreement, that is limiting warming to 1.5 °C above pre-industrial levels, is projected to greatly benefit all of the countries in this study, greatly reducing exposure to severe drought for large percentages of the population and in all major land cover classes, with Egypt potentially benefiting the most.

Definition of a temporal distribution index for high temporal resolution precipitation data over Peninsular Spain and the Balearic Islands: the fractal dimension; and its synoptic implications - Oliver Meseguer-Ruiz; Timothy J. Osborn; Pablo Sarricolea; Philip D. Jones; Jorge Olcina Cantos; Roberto Serrano-Notivoli; Javier Martin-Vide (Climate Dynamics, 2019)

Estimates of the North Atlantic Oscillation back to 1692 using a Paris–London westerly index - Richard C. Cornes; Philip D. Jones; Keith R. Briffa; Timothy J. Osborn (International Journal of Climatology, 2013)
A westerly index for Europe is developed back to 1692 using newly recovered and corrected Mean Sea‐level Pressure (MSLP) data from London and Paris. The index is compared against various instrumental and proxy indices of the North Atlantic Oscillation (NAO). In the winter, the Paris‐London index depicts a spatial pattern of atmospheric circulation that is bi‐modal, with centres of action that are shifted eastwards compared to the NAO. Owing to asymmetry in the NAO the Paris‐London index provides a good depiction of positive NAO conditions as well as extreme negative phases of the NAO that arise from reversals of the pressure centres, but less extreme negative NAO conditions are associated with westerly index values approaching zero. The merit in using the Paris‐London index lies with its consistency over time as a measure of westerly wind flow, which may not be the case with other proxy‐based indices. In the summer, the Paris‐London index bears a close relationship to the reconstructed high‐summer NAO series of Folland et al. ( 2009 ) as well as the summer Luterbacher et al. ( 1999 ) NAO reconstruction. An important finding is that the summer NAO was highly variable during the early nineteenth century but was predominately positive on the decadal time scale during that period. Since circa 1970 the summer index has mostly been negative, indicating reduced westerlies and increased blocking conditions that are exceptional in the context of the last 250 years. Copyright © 2012 Royal Meteorological Society

A daily series of mean sea‐level pressure for Paris, 1670–2007 - Richard C. Cornes; Phil D. Jones; Keith R. Briffa; Timothy J. Osborn (International Journal of Climatology, 2012)
It has been known for some time that the potential exists to construct a long daily series of surface pressure for the city of Paris because of the existence of various instrumental series that might be pieced together. The remarkable weather diary kept by the physician, Louis Morin, sets the start of the potential series to 1670, and various other series have now been digitized and corrected to allow the formation of a daily series of Mean Sea‐Level Pressure (MSLP) that spans the greater part of 300 years. Unfortunately, a gap in the series still exists for the period 1726–1747, where it appears that no barometer observations have survived. This paper discusses the sources of the various pressure data used in the Paris daily MSLP series, and describes how these observations have been corrected and amalgamated to form a near‐continuous, homogeneous series. The data are compared with a similar long daily series that has been independently constructed for the city of London (1692–2007). This comparison indicates that the two MSLP series are of a sufficient quality to provide useful information about the atmospheric circulation across western Europe over the last 300 years. Copyright © 2011 Royal Meteorological Society

A daily series of mean sea‐level pressure for London, 1692–2007 - Richard C. Cornes; Phil D. Jones; Keith R. Briffa; Timothy J. Osborn (International Journal of Climatology, 2012)
This paper presents a new 300‐year daily series of Mean Sea‐Level Pressure (MSLP) for the city of London. Daily barometer readings recorded in the vicinity of London were digitised from several sources and by joining these data with previously available data, a near‐continuous series was constructed to span the period 1692–2007. The data were quality controlled and then corrected to represent daily means of MSLP at standard modern‐day conditions. This series was then subjected to a statistical homogenisation procedure. The Penalized Maximal t ‐test was used with several reference series to identify breakpoints in the series over the period 1780–2007. In the absence of suitable reference series, the homogeneity of the earlier 1692–1779 period was tested using the Penalized Maximal F‐test. Both tests were implemented through the RHtestV2 software on the monthly and annual means derived from the daily data. The majority of the identified breakpoints could be supported by meta‐data and most occur at the juncture of the component series. A major feature of the homogenised series is that the long‐term mean is 1.2 hPa lower than that of the previous monthly series for London created under the EU ADVICE project for the period 1774–1999. The long‐term mean of 1015.2 hPa for the new series is more consistent with other long MSLP series in the UK. Copyright © 2011 Royal Meteorological Society

Seasonality and depth distribution of a mesopelagic foraminifer, Hastigerinella digitata , in Monterey Bay, California - Pincelli M. Hull; Karen J. Osborn; Richard D. Norris; Bruce H. Robison (Limnology and Oceanography, 2011)
We investigated the habitat depth and population dynamics of mesopelagic foraminifera in Monterey Bay, California, using 12 yr of video surveys and specimens from live collections. The water column over Monterey Canyon continuously supports two distinct species of mesopelagic foraminifera, Hastigerinella digitata and a previously unknown species referred to as Hastigerina sp., with H. digitata dominating the planktonic foraminiferal assemblage at mesopelagic depths. H. digitata populations live within a narrow depth horizon that lies above the core of the regional oxygen minimum zone at a depth of 280–358 m and O 2 concentrations of 1–1.3 mL L −1 . Our observations provide a modern calibration for understanding fossil digitate planktonic foraminifera. We observed numerous copepods in various stages of ingestion on the spines of H. digitata and a conspicuous lack of detritus attached to the spine network, providing support for the hypothesis that H. digitata is an obligate carnivore. H. digitata populations did not show the strong two‐phase seasonality that characterizes the population dynamics of many mesopelagic species that live above the Monterey Canyon, although H. digitata was generally more abundant in cooler waters on seasonal and interannual timescales.

The annual cycle of heavy precipitation across the United Kingdom: a model based on extreme value statistics - D. Maraun; H. W. Rust; T. J. Osborn (International Journal of Climatology, 2009)
The annual cycle of extreme 1‐day precipitation events across the UK is investigated by developing a statistical model and fitting it to data from 689 rain gauges. A generalized extreme‐value distribution (GEV) is fit to the time series of monthly maxima, across all months of the year simultaneously, by approximating the annual cycles of the location and scale parameters by harmonic functions, while keeping the shape parameter constant throughout the year. We average the shape parameter of neighbouring rain gauges to decrease parameter uncertainties, and also interpolate values of all model parameters to give complete coverage of the UK. The model reveals distinct spatial patterns for the estimated parameters. The annual mean of the location and scale parameter is highly correlated with orography. The annual cycle of the location parameter is strong in the northwest UK (peaking in late autumn or winter) and in East Anglia (where it peaks in late summer), and low in the Midlands. The annual cycle of the scale parameter exhibits a similar pattern with strongest amplitudes in East Anglia. The spatial patterns of the annual cycle phase suggest that they are linked to the dominance of frontal precipitation for generating extreme precipitation in the west and convective precipitation in the southeast of the UK. The shape parameter shows a gradient from positive values in the east to negative values in some areas of the west. We also estimate 10‐year and 100‐year return levels at each rain gauge, and interpolated across the UK. Copyright © 2008 Royal Meteorological Society

Observed and modelled influence of atmospheric circulation on central England temperature extremes - S. Blenkinsop; P. D. Jones; S. R. Dorling; T. J. Osborn (International Journal of Climatology, 2009)
The regional atmospheric circulation is a major driver of climate for western Europe and so the ability of climate models to accurately simulate its characteristics forms an important part of the rigorous testing of their performance. In this paper we examine the skills of seven regional climate models (RCMs) to reproduce mean daily temperatures for the central England region. Their ability to reproduce observed characteristics of the circulation is then tested using three airflow indices. This is achieved by comparing: (1) the frequency distribution of each index, (2) the relationships between the daily airflow indices and temperature, including daily extremes and (3) the ability of models to reproduce the observed persistence of specific flow regimes and the temperature response to this persistence. It is demonstrated that RCM selection introduces uncertainty into temperature simulations and that there is no single model which outperforms the others. Although the models qualitatively reproduce the observed distributions of the airflow indices reasonably well, most models produce distributions that are statistically significantly different from the observations. In particular, all models overestimate the frequency of winter westerly flow, and biases in the relationships between circulation and temperature are also noted for extreme values of the airflow indices. The persistence of flow regimes is shown to have a significant effect on the observed temperature, though models have difficulty in reproducing the magnitude of the response to this persistence for some flow types. The results presented here not only form a useful model validation exercise but also further highlight the need for the use of multi‐model ensembles in the generation of future climate scenarios. Furthermore, they suggest that the use of atmospheric circulation in statistical downscaling methods might be enhanced by the inclusion of persistence, particularly when producing scenarios of temperature extremes. Copyright © 2008 Royal Meteorological Society

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

United Kingdom daily precipitation intensity: improved early data, error estimates and an update from 2000 to 2006 - D. Maraun; T. J. Osborn; N. P. Gillett (International Journal of Climatology, 2008)
This paper updates the analysis by Osborn et al . of trends in the contribution of heavy events to precipitation in the UK. We spatially extended the previous analysis of 110 rain gauges to a set of 689 rain gauges covering almost the whole UK, and updated the results to November 2006. For each station and season, we calculated ten time series of the contribution of ten precipitation amount categories to the total seasonal precipitation. A principal component analysis of post‐1961 trends of all categories and stations is consistent with earlier results, namely, widespread shifts towards greater contribution from heavier precipitation categories during winter, and towards light and moderate categories during summer. Regional and UK average time series of the contribution from the category consisting of the heaviest events indicate that the increased winter intensity was sustained during the most recent ten years, but the trend did not continue at the rate reported previously for 1961–1995. For summer, the decreasing contribution from the heaviest rainfall category reported for 1961–1995 underwent a reversal during the most recent decade, returning towards the 1961–1995 reference level of intensity. Confidence intervals for these regional and UK average time series were estimated by a bootstrap approach and indicate that the sparser observations from the first half of the 20th century are still sufficient to estimate UK average change. These longer records support the existence of a long‐term increase in winter precipitation intensity, and similar trends have now also become evident in spring and (to a lesser extent) autumn. The summer rainfall intensity has exhibited changes that are more consistent with inter‐decadal variability than any overall trend. Copyright © 2008 Royal Meteorological Society

Respiration rate and cost of swimming for Antarctic krill, Euphausia superba, in large groups in the laboratory - K. M. Swadling; D. A. Ritz; S. Nicol; J. E. Osborn; L. J. Gurney (Marine Biology, 2005)

Probable causes of late twentieth century tropospheric temperature trends - P. W. Thorne; P. D. Jones; S. F. B. Tett; M. R. Allen; D. E. Parker; P. A. Stott; G. S. Jones; T. J. Osborn; T. D. Davies (Climate Dynamics, 2003)

The role of the oceans in climate - G. R. Bigg; T. D. Jickells; P. S. Liss; T. J. Osborn (International Journal of Climatology, 2003)
The ocean is increasingly seen as a vital component of the climate system. It exchanges with the atmosphere large quantities of heat, water, gases, particles and momentum. It is an important part of the global redistribution of heat from tropics to polar regions keeping our planet habitable, particularly equatorward of about 30°. In this article we review recent work examining the role of the oceans in climate, focusing on research in the Third Assessment Report of the IPCC and later. We discuss the general nature of oceanic climate variability and the large role played by stochastic variability in the interaction of the atmosphere and ocean. We consider the growing evidence for biogeochemical interaction of climatic significance between ocean and atmosphere. Air–sea exchange of several radiatively important gases, in particular CO 2 , is a major mechanism for altering their atmospheric concentrations. Some more reactive gases, such as dimethyl sulphide, can alter cloud formation and hence albedo. Particulates containing iron and originating over land can alter ocean primary productivity and hence feedbacks to other biogeochemical exchanges. We show that not only the tropical Pacific Ocean basin can exhibit coupled ocean–atmosphere interaction, but also the tropical Atlantic and Indian Oceans. Longer lived interactions in the North Pacific and Southern Ocean (the circumpolar wave) are also reviewed. The role of the thermohaline circulation in long‐term and abrupt climatic change is examined, with the freshwater budget of the ocean being a key factor for the degree, and longevity, of change. The potential for the Mediterranean outflow to contribute to abrupt change is raised. We end by examining the probability of thermohaline changes in a future of global warming. Copyright © 2003 Royal Meteorological Society

Seasonal variation in top-down and bottom-up processes in a grassland arthropod community - Alison G. Boyer; Robert E. Swearingen; Margo A. Blaha; Christopher T. Fortson; Sara K. Gremillion; Kelly A. Osborn; Matthew D. Moran (Oecologia, 2003)

Polychlorinated Biphenyl (PCB) Congener Concentrations in Seabirds Found Dead in Mortality Incidents Around the British Coast - H. M. Malcolm; D. Osborn; J. Wright; C. L. Wienburg; T. H. Sparks (Archives of Environmental Contamination and Toxicology, 2003)

A multi-proxy holocene record of environmental change fromthe sediments of Skinny Lake, Iskut region, northern British Columbia,Canada - I.S. Spooner; D. Mazzucchi; G. Osborn; R. Gilbert; I. Larocque (Journal of Paleolimnology, 2002)

Evidence for homology of flowering-time genes VFR2 from Brassica rapa and FLC from Arabidopsis thaliana - C. Kole; P. Quijada; S. D. Michaels; R. M. Amasino; T. C. Osborn (Theoretical and Applied Genetics, 2001)

Observed trends in the daily intensity of United Kingdom precipitation - Timothy J. Osborn; Mike Hulme; Philip D. Jones; Tracy A. Basnett (International Journal of Climatology, 2000)

A molecular marker linkage map of tetraploid alfalfa (Medicago sativa L.) - D. J. Brouwer; T. C. Osborn (Theoretical and Applied Genetics, 1999)

Evaluation of the North Atlantic Oscillation as simulated by a coupled climate model - T. J. Osborn; K. R. Briffa; S. F. B. Tett; P. D. Jones; R. M. Trigo (Climate Dynamics, 1999)

Diminished recognition of HLA-A2 proteins lacking a cytoplasmic domain (CY) by A2-restricted, EBV-specific CTLs: possible role of the CY in TAP association - Martin J. Cannon; Criston K. Osborn; Rachel A. Nazaruk; V. Grigoriev; Mark D. Crew (Immunogenetics, 1999)

Gross deletions of the neurofibromatosis type 1 (NF1) gene are predominantly of maternal origin and commonly associated with a learning disability, dysmorphic features and developmental delay - M. Upadhyaya; M. Ruggieri; J. Maynard; M. Osborn; C. Hartog; S. Mudd; M. Penttinen; I. Cordeiro; M. Ponder; B. A. J. Ponder; M. Krawczak; D. N. Cooper (Human Genetics, 1998)

Volatile Compounds from the Forehead Region of Male White-Tailed Deer (Odocoileus virginianus) - J. W. Gassett; D. P. Wiesler; A. G. Baker; D. A. Osborn; K. V. Miller; R. L. Marchinton; M. Novotny (Journal of Chemical Ecology, 1997)

Polychlorinated biphenyl congener patterns in tissues from a selection of British birds - R. S. Boumphrey; S. J. Harrad; K. C. Jones; D. Osborn (Archives of Environmental Contamination and Toxicology, 1993)